Regulation of Cosmetics: What has Malaysia Learnt from the European System? - Zakaria, Z. (Kluwer (now part of Springer), 2015)
Cosmetics are very popular consumer products. Their ever-increasing sales have encouraged many producers to introduce cosmetics which are sometimes unsafe and cause adverse effects. In order to secure the safety of cosmetic products and to make the cosmetics trade more effective, the EU has harmonized its cosmetic regulations. This is the first region in the world to have done so. This harmonization model and many aspects of the EU regulatory framework have been followed and adopted by ASEAN countries as well as others around the world. As Malaysia is an ASEAN Member State, it has also adopted this system. This article takes Malaysia as a case study in order to determine how the EU model has been put into operation. Although there are a lack of resources and technical facilities, ASEAN has certainly benefited from the EU system, but there has also been a need to include additional requirements to tailor the EU Directive to the requirements of ASEAN countries, not least the greater lack of awareness by the public of the composition and dangers of cosmetic products.